The use of BBC English Quizzes Application to enhance EFL students’ motivation in listening (A case study at an English course in Banjar) - Alzahara, Daragita; Herlina, Rina; Irianti, Leni (Journal of English Education Program (JEEP), 2024)
This study investigated the use of BBC English quizzes application that can help students' learning processes at which researchers pay attention to the lack of motivation of students in learning listening. This research aimed to investigate the implementation and students' perceptions of the use of BBC English quizzes application to enhance students' listening skills. This research used a case study employing questionnaires and interviews in the process of collecting data. The participants in this study were selected purposively, namely, students who studied at one of the English courses in Banjar. This research received a positive and effective response at which students feel happier and enthusiastic about learning and listening by using the BBC English quizzes application. The researcher suggests that future researchers who want to know more about the use of the quizzes application to enhance students' motivation in listening skills, should add more students for participants in formal school because they are more numerous.